Dynamics of competition and co-infection between Zoophthora radicans and Pandora blunckii in Plutella xylostella larvae. (October 2015) - Sandoval-Aguilar, José A.; Guzmán-Franco, Ariel W.; Pell, Judith K.; Clark, Suzanne J.; Alatorre-Rosas, Raquel; Santillán-Galicia, Ma. Teresa; Valdovinos-Ponce, Guadalupe
Abstract: Co-inoculation of Zoophthora radicans and Pandora blunckii in Plutella xylostella larvae were investigated. Co-inoculations were made simultaneously or within 4, 8 or 12 hr of each other to achieve different prior residency times; order of inoculation was alternated. The most larvae infected by a particular species occurred when that species was inoculated alone. In co-inoculations, the majority of larvae were infected by only one species; both isolates of Z. radicans always infected more larvae than P. blunckii when they were inoculated last, regardless of prior residency time, while this was only the case for one of the P. blunckii isolates. The proportion of co-infected larvae never exceeded 20 %, and only occurred when both species were inoculated simultaneously or when the prior residency time was 8 hr or less, regardless of the order of inoculation. Prior residency time and order of inoculation affect the likelihood of competing species surviving during co-inoculation. Highlights: Pandora blunckii and Zoophthora radicans both infect Plutella xylostella larvae. One fungal species can displace the other following co-inoculation. Which fungal species is displaced depends on the order of inoculation. Prior residency time affects the number of co-infected larvae. Small differences in residency time result in more co-infected larvae.